2017
DOI: 10.1161/circgenetics.116.001685
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence and Clinical Implication of Double Mutations in Hypertrophic Cardiomyopathy

Abstract: Background-Available data suggests that double mutations in patients with hypertrophic cardiomyopathy are not rare and are associated with a more severe phenotype. Most of this data, however, is based on noncontemporary variant classification. Methods and Results-Clinical data of all hypertrophic cardiomyopathy patients with 2 rare genetic variants were retrospectively reviewed and compared with a group of patients with a single disease-causing variant. Furthermore, a literature search was performed for all st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
31
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 62 publications
9
31
0
2
Order By: Relevance
“…13 Furthermore, several studies have demonstrated that HCM patients carrying multiple pathogenic gene variants have poorer prognosis in terms of earlier disease onset, increased left ventricular hypertrophy, and increased frequency of heart failure and sudden cardiac death, when compared with those carrying a single mutation. 5,6,11,16 Thus, the present case supports previous claims that rare homozygous variants may aggravate the clinical severity of HCM. Our HCM patient with a homozygous missense variant in MYPBC3 needed a heart transplantation, while his brother who also has the variant in homozygosis and the clinical phenotype of HCM will require specific attention at follow-up as there is the possibility of more adverse manifestations of HCM later.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…13 Furthermore, several studies have demonstrated that HCM patients carrying multiple pathogenic gene variants have poorer prognosis in terms of earlier disease onset, increased left ventricular hypertrophy, and increased frequency of heart failure and sudden cardiac death, when compared with those carrying a single mutation. 5,6,11,16 Thus, the present case supports previous claims that rare homozygous variants may aggravate the clinical severity of HCM. Our HCM patient with a homozygous missense variant in MYPBC3 needed a heart transplantation, while his brother who also has the variant in homozygosis and the clinical phenotype of HCM will require specific attention at follow-up as there is the possibility of more adverse manifestations of HCM later.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast to heterozygous pathogenic mutations, homozygous or compound heterozygous truncating pathogenic MYBPC3 variants cause severe neonatal cardiomyopathy, which leads to heart failure and death within the first year of life . Furthermore, several studies have demonstrated that HCM patients carrying multiple pathogenic gene variants have poorer prognosis in terms of earlier disease onset, increased left ventricular hypertrophy, and increased frequency of heart failure and sudden cardiac death, when compared with those carrying a single mutation . Thus, the present case supports previous claims that rare homozygous variants may aggravate the clinical severity of HCM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Munkánkban két patogén mutáció, MYH7 p.Arg719Gln és p.Ser593ProfsTer11-mutáció hordozását dött. A mindkét mutációt hordozó családtagban malig-Új generációs szekvenáláson alapuló adatok szerint mutáció pozitív HCM-populációban 3-19%-ig terjed, átlagban 8% (19). Kisszámú betegcsoportok vizsgálata és esettanulmányok alapján a multiplex mutációt hordozókban súlyosabb klinikai képet, pl.…”
Section: Megbeszélésunclassified